An Alchemical Quest for Universal Knowledge : The ‘Christian Philosophy’ of Jan Baptist Van Helmont (1579-1644) /: The ‘Christian Philosophy’ of Jan Baptist Van Helmont (1579-1644). (2016) - Hedesan, Georgiana D
No abstract available